2018
DOI: 10.1186/s12887-018-1290-9
|View full text |Cite
|
Sign up to set email alerts
|

Agreement test of transcutaneous bilirubin and bilistick with serum bilirubin in preterm infants receiving phototherapy

Abstract: BackgroundThis study compares the minimally invasive Bilistick and a noninvasive method with standard Total Serum Bilirubin (TSB) measurement in preterm newborns receiving phototherapy. We assess the agreement of Transcutaneous Bilirubinometer (TcB) and Bilistick bilirubin measurements with standard TSB measurement in preterm infants receiving phototherapy.MethodsBilirubin was measured by using TcB and Bilistick in 94 preterm infants in RSCM Jakarta Neonatal Ward from October 2016 to March 2017, with gestation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 16 publications
2
36
1
Order By: Relevance
“…Regarding the most premature patients there is controversy about the suitability of placing a patch (given the skin fragility) or not. There are authors such as Cucuy or Roshsiwatmo, who found a good correlation between TSB and TCB on exposed skin measured with the JM-103 bilirubinometer in the sternum, after the initiation of phototherapy in preterm infants [17,23]. Perhaps the immaturity of the cutaneous barrier of the very premature and its dermal kinetics influences these results, favouring that the reading in uncovered skin is more similar to the TSB.…”
Section: ---------------------------------mentioning
confidence: 99%
“…Regarding the most premature patients there is controversy about the suitability of placing a patch (given the skin fragility) or not. There are authors such as Cucuy or Roshsiwatmo, who found a good correlation between TSB and TCB on exposed skin measured with the JM-103 bilirubinometer in the sternum, after the initiation of phototherapy in preterm infants [17,23]. Perhaps the immaturity of the cutaneous barrier of the very premature and its dermal kinetics influences these results, favouring that the reading in uncovered skin is more similar to the TSB.…”
Section: ---------------------------------mentioning
confidence: 99%
“…Several studies have reported that TcB showed a significant correlation with preterm and term infants under and after phototherapy . Radfar et al stated that TcB can be safely used for the evaluation of bilirubin levels in preterm and term infants undergoing phototherapy .…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous studies investigating the predictive accuracy of TcB compared to TSB in term infants during and after phototherapy. However, its predictive accuracy in late‐preterm infants receiving phototherapy has not been established well . Therefore, the aim of our study was to determine the correlation of TcB with TSB in infants receiving phototherapy and the accuracy of TcB for deciding the time to discontinue phototherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The Bilistick method is an in vitro point-of-care diagnostic method for measuring TSB from capillary or venous blood samples [27]. This is a much cheaper method and multiple studies have found it to be an accurate alternative [28,29]. The Bilistick method also has the added advantage of having a much shorter turn-around-time (time interval between specimen collection and reporting of TSB result) compared to serum measurement and even transcutaneous measurement of bilirubin [27].…”
Section: Diagnostic Testingmentioning
confidence: 99%